Explantation of domestic models of posterior chamber phakic intraocular lenses in the development of subcapsular cataract in higly myopic patients: clinical features - G. V. Sorokoletov; E. R. Tumanyan; A. N. Bessarabov; M. A. Soboleva (Российский офтальмологический журнал)
To date, the operation of choice in young patients with high myopia, is the implantation of posterior chamber phakic intraocular lenses (PIOL), provided that there are contraindications to keratorefractive interventions, However, in the late postoperative period, cataracts may occur, which requires the development of surgical tactics for lens explantation with simultaneous phacoemulsification of cataract (FEC) implementation.The purpose is to develop and analyze a method for removing a PIOL through a 2 mm corneal incision in subcapsular cataract cases.Material and methods. Posterior chamber domestic models of PIOL type RSK-1(3) and RSK-3 in 22 patients (37 eyes), implanted in the S.N. FEDOROV “EYE MICROSURGERY” clinic in 1994 – 2001 had to be removed due to the development of secondary cataracts. PIOL stayed in the eye 2 to 26 years (averagely 14.30 ± 1.30 yrs). In all cases, the P IOL was removed followed by FEC with implantation of a posterior chamber IOL. The optical power of the IOL was calculated mainly in such a way that the residual myopic refraction was 2.0–3.0 D.Results. The intraoperative condition of the anterior chamber was stable, the volume of irrigation fluid consumed was within 90–120 ml. No complications were detected in the early and late postoperative periods. The results of dynamic ophthalmological follow up of patients showed that visual acuity without correction and with correction after surgery averaged 0.2 ± 0.1 and 0.60 ± 0.15, respectively.Conclusion. The proposed method of explantation of domestic lenses of S.N. FEDOROV NMRC MNTK “EYE MICROSURGERY” shows that it enables a safe, simple removal of PIOL in the event of secondary subcapsular cataract, which allows achieving high clinical and functional results without overspending the irrigation solution.